First Steps Towards a Sociocultural Psychological Approach to Museum Evolution - Kernahan, Louis Joe (International Review of Theoretical Psychologies, 2026)
This paper proposes the first steps towards a sociocultural psychological approach to museum evolution. First, a short review of museological and related literature is offered to further contextualize the need for an alternative approach. Then, the article offers an exploration of the theoretical musings of imagination and collective memory within the traditions of sociocultural psychology as a developmental science. Here, it is argued that changes and developments of a museal nature are driven by psychological processes across transactions at the micro-, onto-, and sociogenetic levels. These processes are facilitated by the interactions between of a person navigating their sociocultural context, hinging upon intersubjectivity and sociomateriality as core axioms. This approach will be applied to recent writings by museologists regarding museum planning. This paper concludes by suggesting that further research regarding the everyday acts of collective memory as well as the processes of imagination across time is crucial to deepening our understanding of museum development.